Long-term impacts of polyethylene terephthalate (PET) microplastics in membrane bioreactor. (1st December 2022) - Yi, Kaixin; Huang, Jinhui; Li, Xue; Li, Suzhou; Pang, Haoliang; Liu, Zhexi; Zhang, Wei; Liu, Si; Liu, Chunhua; Shu, Wenli
Abstract: Due to the mass production and daily use of plastic products, the potential toxicity of microplastics to the water environment has attracted worldwide attention. In this work, the effect of typical microplastics (PET) on the performance of activated sludge from membrane bioreactors (MBR) was evaluated. The impacts on biological removal efficiency were unconspicuous with continuous dosing of 60 particles/L. However, further investigations revealed that PET particle accumulation caused adverse impacts on settleability and dewaterability. The SVI value increased from 53.3 ml/g MLSS to 69.9 ml/g MLSS and the CST in the PET reactor increased by 22%. Nevertheless, hydrophobicity was reduced by 49.2%. Mechanism studies exposed that the PET microplastics accumulation improved extracellular polymeric substances (EPS) from 116.96 mg/L to 138.70 mg/L and caused cell membrane damage. The abundance and diversity of microbial community reduced in activated sludge in PET reactor compared with control reactor. These phenomena revealed a possible hypothesis that the microplastic particles increased EPS and cytotoxicity of activated sludge. However, the rate of transmembrane pressure (TMP) build-up was significantly mitigated in PET-MBR compared to that in a control-MBR (1.27 folds), which attributes that physical scour of particles may still alleviate membrane contamination in MBR. Highlights: Membrane biofouling was alleviated due to physical scouring of PET particles. The physicochemical properties of sludge were changed after long-term PET exposure. Accumulation of PET particles caused EPS secretion and cell membrane damage. Long-term exposure to PET changed the microbial community of MBR system.